Luminescent ceramic materials based on laser-synthesized europium-stabilized zirconia nanopowders; Ceramics International; Vol. 52, iss. 29, pt. B - Paygin V. D. Vladimir Denisovich; Kostyukov A. I. Anton Ivanovich; Morkhova E. A. Elizaveta Aleksandrovna; Deulina D. E. Darjya Evgenjevna; Nashivochnikov A.; Suprun E. A. Evgeniy Aleksandrovich; Dvilis E. S. Edgar Sergeevich (2025, 2025)
ZrO2-based materials are considered the gold standard for the manufacturing of ceramic materials used in various applications. Spark plasma sintering has been successfully applied to the fabrication of europium-stabilized zirconia (ESZ) ceramic materials from nanopowders synthesized by laser vaporization. Structural, morphological (XRD and SEM), mechanical, and spectroscopic (photoluminescence) analysis have been used to investigate the influence of the stabilizer (Eu3+) content on ceramics phase composition, crystallite size, relative density, mechanical, and luminescent properties of the ESZ-ceramic materials. The theoretical analysis of the conductive properties of europium-stabilized zirconia with varying Eu concentrations has been conducted. To achieve this, a fast geometrical-topological (GT) method, the bond valence site energy (BVSE) approach, and kinetic Monte Carlo simulation were used. It has been shown that the initial nanostructured ESZ powders have high purity, an average particle size from 11 to 14 nm, agglomerate sizes from 171 to 458 nm, and a specific surface area from 70.11 to 84.85 m2g-1. It has been found that powders, prepared by the laser vaporization method, are of practical interest for manufacturing ESZ-ceramic materials without the use of additional stabilizing additives or activators and can be considered potential promising materials for luminescent applications, such as luminescence sensors, light sources, biotechnology and as solid electrolyte due to its conductive properties